Flame-retardant silicon carbide ceramic rubber material and preparation method thereof
By adding additives such as MIL-100 (Fe,Co)@CSiCNS and modified mica powder to the silicone rubber composite, silicon carbide ceramic rubber material with high flame retardant performance and ceramicization ability was prepared, which solved the problem of insufficient performance of existing materials in the fire field.
Patent Information
- Application Number
- CN202411798711.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The flame retardant performance and ceramicization capabilities of existing silicone rubber composite materials in the fire field are insufficient, making it difficult to meet the safety protection needs of key facilities.
Using methylvinyl silicone rubber as the matrix, adding MIL-100 (Fe,Co)@CSiCNS and modified mica powder and other additives, the flame-retardant silicon carbide ceramic rubber material is prepared through kneading and kneading processes.
The flame retardant properties and ceramicization capabilities of rubber materials are significantly improved, forming a hard ceramic body, and enhancing the material's high temperature, corrosion and wear resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber materials, and in particular to a flame retardant silicon carbide ceramic rubber material and a preparation method thereof. Background Art
[0002] Ceramic rubber material is a new type of refractory material, usually composed of rubber material, ceramic filler, vulcanizing agent, co-solvent and structure control agent and other additives, and then prepared by melt blending. Commonly used rubber materials in ceramic rubber materials include butyl rubber, fluororubber, butanone rubber and silicone rubber. Among them, the ceramic rubber material prepared with silicone rubber as the matrix has certain wear resistance, high temperature resistance, corrosion resistance, insulation and flame retardant properties. However, adding only commonly used ceramic fillers and ceramic aids is not enough to make silicone rubber composites have good flame retardant properties and ceramicization ability, which is not conducive to safety protection in fire scenes.
[0003] Ceramicization of rubber materials is an effective method to improve the fire resistance of rubber, which helps to obtain a hard, durable and porous ceramic shell during high-temperature combustion, covering the surface of the material. On the one hand, it can prevent further combustion of the matrix under the surface, and on the other hand, the ceramic shell can withstand external shock and vibration. Therefore, it is of great significance to study and prepare silicone rubber composites with higher flame retardancy and ceramicization capabilities for the safety protection of key facilities. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a flame retardant silicon carbide ceramic rubber material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A flame retardant silicon carbide ceramic rubber material, comprising the following raw materials in parts by weight: 80-100 parts of methyl vinyl silicone rubber, 15-25 parts of MIL-100(Fe,Co)@CSiCNS, 20-50 parts of modified mica powder, 2-6 parts of boron trioxide, 8-12 parts of hydroxy silicone oil, 2-4 parts of coupling agent, and 1.5-2.5 parts of vulcanizing agent;
[0007] Further, the vulcanizing agent is one or both of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and diisopropylbenzene peroxide;
[0008] Further, the coupling agent is one or two of KH-550, KH-560 or KH-570;
[0009] The MIL-100(Fe,Co)@CSiCNS is prepared by the following steps:
[0010] Step A1, adding silicon carbide nanosheets to a 1.5-2.5 mol / L hydrochloric acid solution and stirring for 2-3 hours, centrifuging, washing, and drying, collecting the pre-treated silicon carbide nanosheets, and then dispersing the pre-treated silicon carbide nanosheets in deionized water, ultrasonically treating for 0.5-1.5 hours, and then adding chloroacetic acid and ultrasonically stirring for 2-3 hours, centrifuging, washing, and freeze-drying to obtain carboxylated silicon carbide nanosheets (CSiCNS);
[0011] Step A2, ferric nitrate nonahydrate, cobalt nitrate hexahydrate, tris-benzoic acid and deionized water are mixed and stirred evenly, and then carboxylated silicon carbide nanosheets are added, stirred in a water bath at 55-65° C. for 1 hour, and then transferred to an autoclave, reacted at 100-120° C. for 8-12 hours, filtered, washed and dried to obtain MIL-100(Fe,Co)@CSiCNS (MIL-100(Fe,Co) loaded with carboxylated silicon carbide nanosheets);
[0012] Furthermore, in step A1, the ratio of the amount of silicon carbide nanosheets to the hydrochloric acid solution is 1-3 g: 3-6 mL;
[0013] Furthermore, in the step A1, the ratio of the pre-treated silicon carbide nanosheets, deionized water and chloroacetic acid is 0.5-1.5 g: 100 mL: 5-10 g;
[0014] Furthermore, in step A2, the usage ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, tris-benzoic acid, deionized water and carboxylated silicon carbide nanosheets is 1-2 g: 0.1-0.3 g: 0.8-1.8 g: 50 mL.
[0015] The modified mica powder is prepared by the following steps:
[0016] Step B1, add 1-vinylimidazole, diphenyl phosphite and azobisisobutyronitrile into a flask containing toluene, mix and stir evenly, heat to 60-80° C., stir and react for 6-10 hours, filter, and obtain a phosphorus-containing product;
[0017] Step B2, adding acetone to the phosphorus-containing product, and heating to 45° C., then slowly adding 1,4-dichlorobutane dropwise, stirring and reacting for 10 hours, filtering, rotary evaporating, and drying to obtain a quaternary ammonium phosphorus-containing derivative;
[0018] Step B3, ultrasonically stirring the mica powder in deionized water for 0.5-1.5h, then heating to 75°C and stirring for 3-6h, then transferring to an ice water bath, slowly adding an aqueous solution of a quaternary ammonium phosphorus derivative, stirring for 5-7h, filtering, washing, and drying to obtain modified mica powder;
[0019] Further, in step B1, the usage ratio of 1-vinylimidazole, diphenyl phosphite, azobisisobutyronitrile and toluene is 0.05-0.15 mol: 0.05-0.15 mol: 0.16-0.49 g: 200 mL;
[0020] Further, the amount ratio of 1,4-dichlorobutane, acetone in step B2 and 1-vinylimidazole in step B1 is 0.025-0.075 mol: 100 mL: 0.05-0.15 mol;
[0021] Furthermore, in step B3, the mica powder, deionized water and quaternized phosphorus-containing derivative aqueous solution are used in a ratio of 0.5-2 g: 80 mL: 20 mL, and the quaternized phosphorus-containing derivative aqueous solution is prepared by mixing and stirring the quaternized phosphorus-containing derivative and deionized water in a ratio of 0.1-0.3 g: 20 mL.
[0022] A method for preparing a flame retardant silicon carbide ceramic rubber material comprises the following steps:
[0023] Step S1, weighing raw materials by weight, adding methyl vinyl silicone rubber, modified mica powder, MIL-100(Fe,Co)@CSiCNS, hydroxy silicone oil, coupling agent and boron trioxide into a kneader in sequence, kneading at 60-80° C. for 1-2 hours, then heating to 110-130° C., continuing to knead for 1-2 hours, evacuating, discharging, cooling, and obtaining a mixed rubber material;
[0024] Step S2, kneading the mixed rubber material in an open mill, and adding a vulcanizing agent and kneading for 10-15 minutes to obtain a flame retardant silicon carbide ceramic rubber material.
[0025] Beneficial effects of the present invention:
[0026] The flame-retardant silicon carbide ceramic rubber material of the present invention is prepared by taking methyl vinyl silicone rubber as the main matrix material, adding MIL-100(Fe,Co)@CSiCNS, modified mica powder and other additives, and not only has the excellent high temperature resistance and corrosion resistance of silicone rubber, but also has the excellent wear resistance of ceramic materials; wherein, MIL-100(Fe,Co)@CSiCNS is prepared by modifying silicon carbide nanosheets as the substrate, and acts as an inorganic flame retardant component in the matrix, thereby improving the flame retardant property of the rubber material; the modified mica powder acts as a ceramic filler, which not only gives the matrix certain flame retardant property, but also can undergo melting and eutectic reaction with silicone rubber at high temperature to form a hard ceramic body, thereby further improving the flame retardant property of the matrix.
[0027] The MIL-100(Fe,Co)@CSiCNS prepared by the present invention comprises the following steps: firstly treating SiCNS with hydrochloric acid to obtain a pre-treated SiCNS containing hydroxyl groups on the surface; then reacting the hydroxyl groups on the surface of the pre-treated SiCNS with chloroacetic acid to obtain CSiCNS; and then using ferric nitrate nonahydrate, cobalt nitrate hexahydrate and tris-benzoic acid as raw materials to load MIL-100(Fe,Co) on CSiCNS through a hydrothermal reaction to obtain MIL-100(Fe,Co)@CSiCNS. The introduction of MIL-100(Fe,Co)@CSiCNS can significantly improve the flame retardant properties of the matrix by utilizing the synergistic effect between MIL-100(Fe,Co) and CSiCNS. This is because the layered silicon carbide nanosheets have a good physical barrier effect. During the combustion process, a protective layer is formed to isolate the heat transfer and prevent the substrate from contacting oxygen, thereby playing a flame retardant role. At the same time, non-flammable or non-combustible gases (such as water vapor, ammonia and nitrogen, etc.) are released. These gases can reduce the oxygen concentration around the matrix, slow down and inhibit the progress of the combustion reaction. line; and MIL-100 (Fe, Co) will produce metal oxides with catalytic effect during the combustion process of the matrix, which can promote the breakage of Si-CH3 in the matrix and the coupling of free radicals, forming a Si-C-Si cross-linked structure, making the silica produced by combustion more compact, effectively reducing the overflow of smoke particles into the air, and has the effect of blocking oxygen and inhibiting the generation of smoke; in addition, the addition of SiCNS can not only be used as a filler, significantly improving the hardness and strength of the rubber material, making it more wear-resistant, but also improve its high temperature resistance, so that it can still maintain good performance in high temperature environment.
[0028] In the modified mica powder, the double bond in 1-vinyl imidazole and the active hydrogen in diphenyl phosphite are firstly reacted to obtain a phosphorus-containing product; then the chlorine group in 1,4-dichlorobutane and the tertiary amine group in the phosphorus-containing product are reacted to obtain a quaternized phosphorus-containing derivative; finally, the mica powder is intercalated and modified by the diquaternary ammonium salt cation contained in the quaternized phosphorus-containing derivative to obtain the modified mica powder. The modified mica powder is added to the matrix to improve its dispersibility in the matrix, reduce the performance degradation caused by agglomeration, and has a better reinforcement effect. At the same time, the modified mica powder with good dispersibility acts as a ceramic filler in the matrix, and can melt and eutectic react with silicone rubber at high temperature to form a hard ceramic body, further improving the flame retardant properties of the matrix; in addition, after the mica powder is intercalated and modified, its interlayer or surface contains phosphite and imidazole structures, which can work synergistically to further improve the flame retardant and smoke suppression properties of the matrix. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1: MIL-100(Fe,Co)@CSiCNS was prepared by the following steps:
[0031] Step A1, adding 1g of silicon carbide nanosheets to 3mL of 2.5mol / L hydrochloric acid solution and stirring for 2h, centrifuging, washing, and drying, collecting the pretreated silicon carbide nanosheets, and then dispersing 0.5g of the pretreated silicon carbide nanosheets in 100mL of deionized water, ultrasonically treating for 0.5h, and then adding 5g of chloroacetic acid and ultrasonically stirring for 2h, centrifuging, washing, and freeze-drying to obtain carboxylated silicon carbide nanosheets;
[0032] Step A2: 1 g of ferric nitrate nonahydrate, 0.1 g of cobalt nitrate hexahydrate, 0.8 g of tris-benzoic acid and 50 mL of deionized water were mixed and stirred evenly, and then carboxylated silicon carbide nanosheets were added, stirred in a water bath at 55 ° C for 1 h, and then transferred to an autoclave, reacted at 100 ° C for 8 h, filtered, washed and dried to obtain MIL-100 (Fe, Co) @ CSiCNS.
[0033] The modified mica powder is prepared by the following steps:
[0034] Step B1, add 0.05 mol 1-vinylimidazole, 0.05 mol diphenyl phosphite and 0.16 g azobisisobutyronitrile into a flask containing 200 mL toluene, mix and stir evenly, heat to 60° C., stir and react for 6 hours, filter, and obtain a phosphorus-containing product;
[0035] Step B2, add 100 mL of acetone to the phosphorus-containing product, raise the temperature to 45° C., then slowly dropwise add 0.025 mol of 1,4-dichlorobutane, stir and react for 10 h, filter, rotary evaporate, and dry to obtain a quaternary ammonium phosphorus-containing derivative;
[0036] Step B3, ultrasonically stir 0.5 g of mica powder in 80 mL of deionized water for 0.5 h, then heat to 75 ° C and stir for 3 h, then transfer to an ice water bath, slowly add 20 mL of a quaternary ammonium phosphorus derivative aqueous solution, stir and react for 5 h, filter, wash and dry to obtain modified mica powder. The quaternary ammonium phosphorus derivative aqueous solution is prepared by mixing and stirring a quaternary ammonium phosphorus derivative and deionized water in a dosage ratio of 0.1 g: 20 mL.
[0037] Example 2: MIL-100(Fe,Co)@CSiCNS was prepared by the following steps:
[0038] Step A1, adding 2 g of silicon carbide nanosheets to 4.5 mL of 2 mol / L hydrochloric acid solution and stirring for 2.5 h, centrifuging, washing, and drying, collecting the pre-treated silicon carbide nanosheets, and then dispersing 1 g of the pre-treated silicon carbide nanosheets in 100 mL of deionized water, ultrasonically treating for 1 h, and then adding 7.5 g of chloroacetic acid and ultrasonically stirring for 2.5 h, centrifuging, washing, and freeze-drying to obtain carboxylated silicon carbide nanosheets;
[0039] Step A2: 1.5 g of ferric nitrate nonahydrate, 0.2 g of cobalt nitrate hexahydrate, 1.3 g of tris-benzoic acid and 50 mL of deionized water were mixed and stirred evenly, and then carboxylated silicon carbide nanosheets were added, stirred in a water bath at 60 ° C for 1 h, and then transferred to an autoclave, reacted at 110 ° C for 10 h, filtered, washed and dried to obtain MIL-100 (Fe, Co) @ CSiCNS.
[0040] The modified mica powder is prepared by the following steps:
[0041] Step B1, add 0.1 mol 1-vinylimidazole, 0.1 mol diphenyl phosphite and 0.32 g azobisisobutyronitrile into a flask containing 200 mL toluene, mix and stir evenly, heat to 70° C., stir and react for 8 h, filter, and obtain a phosphorus-containing product;
[0042] Step B2, add 100 mL of acetone to the phosphorus-containing product, raise the temperature to 45° C., then slowly dropwise add 0.05 mol of 1,4-dichlorobutane, stir and react for 10 h, filter, rotary evaporate, and dry to obtain a quaternary ammonium phosphorus-containing derivative;
[0043] Step B3, ultrasonically stir 1 g of mica powder in 80 mL of deionized water for 1 h, then heat to 75 ° C and stir for 4.5 h, then transfer to an ice water bath, slowly add 20 mL of a quaternary ammonium phosphorus derivative aqueous solution, stir and react for 6 h, filter, wash and dry to obtain modified mica powder. The quaternary ammonium phosphorus derivative aqueous solution is prepared by mixing and stirring a quaternary ammonium phosphorus derivative and deionized water in a dosage ratio of 0.2 g: 20 mL.
[0044] Example 3: MIL-100(Fe,Co)@CSiCNS was prepared by the following steps:
[0045] Step A1, adding 3 g of silicon carbide nanosheets to 6 mL of 1.5 mol / L hydrochloric acid solution and stirring for 3 h, centrifuging, washing, and drying, collecting the pre-treated silicon carbide nanosheets, and then dispersing 1.5 g of the pre-treated silicon carbide nanosheets in 100 mL of deionized water, ultrasonically treating for 1.5 h, and then adding 10 g of chloroacetic acid and ultrasonically stirring for 3 h, centrifuging, washing, and freeze-drying to obtain carboxylated silicon carbide nanosheets;
[0046] Step A2: 2 g of ferric nitrate nonahydrate, 0.3 g of cobalt nitrate hexahydrate, 1.8 g of tris-benzoic acid and 50 mL of deionized water were mixed and stirred evenly, and then carboxylated silicon carbide nanosheets were added, stirred in a water bath at 65 ° C for 1 h, and then transferred to an autoclave, reacted at 120 ° C for 12 h, filtered, washed and dried to obtain MIL-100 (Fe, Co) @ CSiCNS.
[0047] The modified mica powder is prepared by the following steps:
[0048] Step B1, add 0.15 mol 1-vinylimidazole, 0.15 mol diphenyl phosphite and 0.49 g azobisisobutyronitrile into a flask containing 200 mL toluene, mix and stir evenly, heat to 80° C., stir and react for 10 hours, filter, and obtain a phosphorus-containing product;
[0049] Step B2, add 100 mL of acetone to the phosphorus-containing product, raise the temperature to 45° C., then slowly dropwise add 0.075 mol of 1,4-dichlorobutane, stir and react for 10 h, filter, rotary evaporate, and dry to obtain a quaternary ammonium phosphorus-containing derivative;
[0050] Step B3, ultrasonically stir 2 g of mica powder in 80 mL of deionized water for 1.5 h, then heat to 75 ° C and stir for 6 h, then transfer to an ice water bath, slowly add 20 mL of a quaternary ammonium phosphorus derivative aqueous solution, stir and react for 7 h, filter, wash and dry to obtain modified mica powder. The quaternary ammonium phosphorus derivative aqueous solution is prepared by mixing and stirring a quaternary ammonium phosphorus derivative and deionized water in a dosage ratio of 0.3 g: 20 mL.
[0051] Embodiment 4: A method for preparing a flame retardant silicon carbide ceramic rubber material comprises the following steps:
[0052] 80 parts of methyl vinyl silicone rubber, 15 parts of MIL-100(Fe,Co)@CSiCNS prepared in Example 1, 20 parts of modified mica powder prepared in Example 1, 2 parts of boron trioxide, 8 parts of hydroxy silicone oil, 2 parts of KH-550, and 1.5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;
[0053] Step S1, weighing raw materials by weight, adding methyl vinyl silicone rubber, modified mica powder prepared in Example 1, MIL-100(Fe,Co)@CSiCNS prepared in Example 1, hydroxy silicone oil, KH-550 and boron trioxide into a kneader in sequence, kneading at 60° C. for 1 h, then heating to 110° C., kneading for another 1 h, evacuating, discharging, cooling, and obtaining a mixed rubber material;
[0054] Step S2, kneading the mixed rubber material in an open mill, adding 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and kneading for 10 minutes to obtain a flame retardant silicon carbide ceramic rubber material.
[0055] Embodiment 5: A method for preparing a flame retardant silicon carbide ceramic rubber material comprises the following steps:
[0056] 90 parts of methyl vinyl silicone rubber, 20 parts of MIL-100(Fe,Co)@CSiCNS prepared in Example 2, 35 parts of modified mica powder prepared in Example 2, 4 parts of boron trioxide, 10 parts of hydroxy silicone oil, 3 parts of KH-560, and 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;
[0057] Step S1, weighing raw materials by weight, adding methyl vinyl silicone rubber, modified mica powder prepared in Example 2, MIL-100(Fe,Co)@CSiCNS prepared in Example 2, hydroxy silicone oil, KH-560 and boron trioxide into a kneader in sequence, kneading at 70° C. for 1.5 h, then heating to 120° C., kneading for 1.5 h, evacuating, discharging, cooling, and obtaining a mixed rubber material;
[0058] Step S2, kneading the mixed rubber material in an open mill, adding dicumyl peroxide and kneading for 10-15 minutes to obtain a flame retardant silicon carbide ceramic rubber material.
[0059] Embodiment 6: A method for preparing a flame retardant silicon carbide ceramic rubber material comprises the following steps:
[0060] 100 parts of methyl vinyl silicone rubber, 25 parts of MIL-100(Fe,Co)@CSiCNS prepared in Example 3, 50 parts of modified mica powder prepared in Example 3, 6 parts of boron trioxide, 12 parts of hydroxy silicone oil, 4 parts of KH-570, and 2.5 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane;
[0061] Step S1, weighing raw materials by weight, adding methyl vinyl silicone rubber, modified mica powder prepared in Example 3, MIL-100(Fe,Co)@CSiCNS prepared in Example 3, hydroxy silicone oil, KH-570 and boron trioxide into a kneader in sequence, kneading at 80° C. for 2 h, then heating to 130° C., kneading for another 2 h, evacuating, discharging, cooling, and obtaining a mixed rubber material;
[0062] Step S2, kneading the mixed rubber material in an open mill, adding dicumyl peroxide and kneading for 15 minutes to obtain a flame retardant silicon carbide ceramic rubber material.
[0063] Comparative Example 1: This comparative example is a ceramic rubber material. The difference from Example 6 is that silicon carbide nanosheets are used instead of the MIL-100(Fe,Co)@CSiCNS prepared in Example 3, and the rest are the same.
[0064] Comparative Example 2: This comparative example is a ceramic rubber material. The difference from Example 6 is that mica powder is used instead of the modified mica powder prepared in Example 3, and the rest is the same.
[0065] The ceramic rubber materials prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:
[0066] Hardness test: Test in accordance with GB / T 531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore hardness tester method (Shore hardness)";
[0067] Flame retardant performance test: According to GB / T 10707-2008 test limit oxygen index value (LOI);
[0068] Mechanical properties test: tensile strength and elongation at break were tested according to GB / T 528-2009 standard;
[0069] Ceramic performance test: The ceramic rubber materials in Examples 4-6 and Comparative Examples 1-2 were heated at 800° C. for 50 min to form a ceramic body, and the appearance of the ceramic body was observed;
[0070] The test results are shown in Table 1:
[0071] Table 1: Performance test results Hardness LOI Tensile strength (MPa) Elongation at break (%) Ceramic properties Example 4 75 39.5 6.8 423 Ceramic layer is tight and hard Example 5 77 40.1 7.2 437 Ceramic layer is tight and hard Example 6 80 41.0 7.7 452 Ceramic layer is tight and hard Comparative Example 1 49 27.3 3.6 316 Loose ceramic layer Comparative Example 2 51 28.5 3.7 338 Loose ceramic layer
[0072] It can be seen from Table 1 that the ceramic rubber material prepared by the present invention has excellent mechanical properties, flame retardant properties and hardness, and can form a compact and hard ceramic body after high-temperature calcination.
[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A flame retardant silicon carbide ceramic rubber material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of methyl vinyl silicone rubber, 15-25 parts of MIL-100(Fe,Co)@CSiCNS, 20-50 parts of modified mica powder, 2-6 parts of boron trioxide, 8-12 parts of hydroxy silicone oil, 2-4 parts of coupling agent and 1.5-2.5 parts of vulcanizing agent; The MIL-100(Fe,Co)@CSiCNS is prepared by the following steps: Step A1, adding silicon carbide nanosheets to a 1.5-2.5 mol / L hydrochloric acid solution and stirring for 2-3 hours, centrifuging, washing, and drying, collecting the pre-treated silicon carbide nanosheets, and then dispersing the pre-treated silicon carbide nanosheets in deionized water, ultrasonically treating for 0.5-1.5 hours, and then adding chloroacetic acid and ultrasonically stirring for 2-3 hours, centrifuging, washing, and freeze-drying to obtain carboxylated silicon carbide nanosheets; Step A2: Mix ferric nitrate nonahydrate, cobalt nitrate hexahydrate, tris-benzoic acid and deionized water and stir evenly, then add carboxylated silicon carbide nanosheets, stir in a water bath at 55-65° C. for 1 h, transfer to an autoclave, react at 100-120° C. for 8-12 h, filter, wash and dry to obtain MIL-100(Fe,Co)@CSiCNS.
2. The flame retardant silicon carbide ceramic rubber material according to claim 1, characterized in that: In step A1, the ratio of silicon carbide nanosheets to hydrochloric acid solution used in the pretreatment of silicon carbide nanosheets is 1-3 g: 3-6 mL.
3. The flame retardant silicon carbide ceramic rubber material according to claim 1, characterized in that: In step A1, the amount ratio of the pre-treated silicon carbide nanosheets, deionized water and chloroacetic acid in the carboxylation of silicon carbide nanosheets is 0.5-1.5 g: 100 mL: 5-10 g.
4. The flame retardant silicon carbide ceramic rubber material according to claim 1, characterized in that: In step A2, the usage ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, tris-benzoic acid, deionized water and carboxylated silicon carbide nanosheets is 1-2 g: 0.1-0.3 g: 0.8-1.8 g: 50 mL.
5. The flame retardant silicon carbide ceramic rubber material according to claim 1, characterized in that: The modified mica powder is prepared by the following steps: Step B1, add 1-vinylimidazole, diphenyl phosphite and azobisisobutyronitrile into a flask containing toluene, mix and stir evenly, heat to 60-80° C., stir and react for 6-10 hours, filter, and obtain a phosphorus-containing product; Step B2, add acetone to the phosphorus-containing product, raise the temperature to 45° C., then slowly drop 1,4-dichlorobutane, stir and react for 10 hours, filter, rotary evaporate, and dry to obtain a quaternary ammonium phosphorus-containing derivative; Step B3, ultrasonically stir the mica powder in deionized water for 0.5-1.5h, then heat to 75°C and stir for 3-6h, then transfer to an ice water bath, slowly add the quaternary ammonium phosphorus derivative aqueous solution, stir to react for 5-7h, filter, wash and dry to obtain the modified mica powder.
6. The flame retardant silicon carbide ceramic rubber material according to claim 5, characterized in that: In step B1, the usage ratio of 1-vinylimidazole, diphenyl phosphite, azobisisobutyronitrile and toluene is 0.05-0.15 mol: 0.05-0.15 mol: 0.16-0.49 g: 200 mL.
7. The flame retardant silicon carbide ceramic rubber material according to claim 5, characterized in that: The usage ratio of 1,4-dichlorobutane, acetone in step B2 and 1-vinylimidazole in step B1 is 0.025-0.075 mol:100 mL:0.05-0.15 mol.
8. The flame retardant silicon carbide ceramic rubber material according to claim 5, characterized in that: In step B3, the mica powder, deionized water and the quaternized phosphorus-containing derivative aqueous solution are used in a ratio of 0.5-2 g: 80 mL: 20 mL, and the quaternized phosphorus-containing derivative aqueous solution is prepared by mixing and stirring the quaternized phosphorus-containing derivative and deionized water in a ratio of 0.1-0.3 g: 20 mL.
9. The flame retardant silicon carbide ceramic rubber material according to claim 1, characterized in that: The vulcanizing agent is one or both of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and diisopropylbenzene peroxide, and the coupling agent is one or both of KH-550, KH-560 or KH-570.
10. A method for preparing the flame retardant silicon carbide ceramic rubber material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, adding methyl vinyl silicone rubber, modified mica powder, MIL-100(Fe,Co)@CSiCNS, hydroxy silicone oil, coupling agent and boron trioxide into a kneader in sequence, kneading at 60-80° C. for 1-2 hours, then heating to 110-130° C., continuing to knead for 1-2 hours, evacuating, discharging, cooling, and obtaining a mixed rubber material; Step S2, kneading the mixed rubber material in an open mill, and adding a vulcanizing agent and kneading for 10-15 minutes to obtain a flame retardant silicon carbide ceramic rubber material.
Citation Information
Patent Citations
Complex comprising crystalline hybrid nanoporous material powder
CN103946161A
Flame-retardant compound, flame-retardant epoxy resin and flame-retardant composition
CN105348563A
Ceramization silicon resin composition and prepreg and laminated board made of the same
CN105778504A
Preparation method of composite water lubricated bearing material
CN108410054A
Porcelainizable halogen-free flame-retardant silicone rubber and preparation method thereof
CN110845850A
Cited By
Silicone rubber thermal insulation material for heater and preparation method of silicone rubber thermal insulation material
CN120648246A